2015
DOI: 10.1089/lrb.2014.0039
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Contrast-Enhanced Magnetic Resonance Lymphangiography of the Upper Limbs in Breast Cancer Related Lymphedema: An Exploratory Study

Abstract: Background: Contrast-Enhanced Magnetic Resonance Lymphangiography (CE-MRL) presents some limitations: (i) it does not quantify lymphatic functionality; and (ii) enhancement of vascular structures may confound image interpretation. Furthermore, although CE-MRL is well described in the published literature for the lower limbs, there is a paucity of data with regards to its use in the upper limbs. In this proof-of-principle study, we propose a new protocol to perform CE-MRL in the upper limbs of patients with bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Reduced lymphatic processing capacity is also consistent with clinical symptoms of lymphedema that occur in advanced stages of lipedema. The relationship between lymphatic function and tissue sodium storage remains to be evaluated in vivo, although these studies may be possible with the emergence of lymphatic imaging modalities including indocyanine green near-infrared imaging 26 , 27 and magnetic resonance lymphangiography 28 30 . Noninvasive lymphangiography approaches 28 , 29 which exploit contrast derived from the long magnetic resonance relaxation times of lymphatic fluid relative to other tissues, may have particular relevance in this field as they can be performed in ten minutes or less and without exogenous contrast agents, thereby making them ideal candidates for surveillance imaging or evaluating therapy responses.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced lymphatic processing capacity is also consistent with clinical symptoms of lymphedema that occur in advanced stages of lipedema. The relationship between lymphatic function and tissue sodium storage remains to be evaluated in vivo, although these studies may be possible with the emergence of lymphatic imaging modalities including indocyanine green near-infrared imaging 26 , 27 and magnetic resonance lymphangiography 28 30 . Noninvasive lymphangiography approaches 28 , 29 which exploit contrast derived from the long magnetic resonance relaxation times of lymphatic fluid relative to other tissues, may have particular relevance in this field as they can be performed in ten minutes or less and without exogenous contrast agents, thereby making them ideal candidates for surveillance imaging or evaluating therapy responses.…”
Section: Discussionmentioning
confidence: 99%
“…Acquiring separate venographic images, with or without contrast, may improve visual conspicuity of veins or be used as subtraction masks for MRL data. Image registration may be necessary to reduce potentially confounding subtraction artifacts, however 8,64 . Noncontrast venograms were produced using balanced steady‐state free precession (bSSFP) by Mazzei et al 27 .…”
Section: Discussionmentioning
confidence: 99%
“…GBCA is most commonly administered undiluted in CE studies; however, as described previously, Borri et al . propose injections heavily diluted with saline such that each milliliter of injected solution contained 0.02 mL of contract agent, 0.1 mL of anesthetic and 0.88 mL saline 8 . Krishnamurthy et al .…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing research seeking to identify the ideal test for lymphatic function in patients, but lymphoscintigraphy and ICG lymphangiography, similar to that performed in mice in this study, have been shown to be effective means of objective and noninvasive detection of early lymphatic disease (37). Magnetic resonance lymphangiography is also a promising diagnostic option, but is not yet widely available (38, 39). Ultimately, patients who are found to have pre-operative lymphatic dysfunction may then undergo therapeutic measures to increase lymphatic functional reserve prior to surgery and/or be considered for prophylactic options to prevent secondary lymphedema entirely.…”
Section: Discussionmentioning
confidence: 99%